Tradisi HANTA UA PUA sebagai Upaya Pelestarian Budaya Religi Di BIMA - Nurrofika Nurrofika; Mukhamad Murdiono (Universitas Andalas, 2020)
Bima has many traditions and local wisdom that should continuously preserve, one of which is the traditional ceremonies of Hanta Ua Pua. This tradition is one of the Bima conventional ceremonies in the context of enlivening the birthday of the great prophet Muhammad. The purpose of writing this article is to find out the implementation and values contained in the Hanta Ua Pua traditional ceremonial religious tradition as an effort to preserve Islamic culture in Bima. This article prepares using the method of library research, which is a method of data collection that is carriers out by utilizing the sources and materials of the library. The results and conclusions obtained are the traditional ceremonies of the Hanta Ua Pua ceremony, which are a memorial and a tribute event to the teachings of Islam and scholars. Done since the Sultanate of Bima. The values in this ceremony divide into three, namely social values, spiritual values, and educational values. The Hanta Ua Pua traditional ceremonies are evidence of the entrance and development of Islamic culture in Bima, which is expected to grow and develop the character of the Bima people who can continue to hold fast to Islamic teachings. However, along with the times, the ceremony began to fade in Bima.